“Now, I have a voice”: Decolonizing intercultural competence through international student leadership - Bui, Tram-Anh (Journal of International Students, 2026)
This study reimagines international education by exploring how international graduate student leaders develop intercultural competence (IC) through a decolonial lens. While IC is often framed within Western-centric paradigms, this research repositions IC via a non-dominant perspective illuminated by Thich Nhat Hanh’s Engaged Buddhism (Thich, 2020). Guided by an innovative, contemplative, and mindfulness-based inquiry, the study examined the perspectives of eight international student leaders from two Canadian institutions. From this foundation, an original Lotus framework emerges through the integration of transformative learning (Mezirow, 1978, 1997) and story-based exploration (Drake, 2010; Drake et al., 1992). The framework advances existing IC scholarship by bridging contemplative epistemologies and decolonial perspectives to reconceptualize IC as a relational and reflective process. This creates a path for IC to (re)construct from the lived experiences of marginalized individuals rather than from a predefined set of competencies.